(untitled) (Medico Legal Update, 2021)
Introduction: Depression is a typical, constant, and debilitating issue occurring during adolescence and influencing near a fourth of all grown-ups. In adolescents, depression related with impaired social connections, lower educational accomplishment, poor scholarly execution, family and social brokenness, physical sick wellbeing and expanded danger of self-destruction. Music therapy intervention could essentially diminished symptoms of depression, increased cognitive functioning and improved quality of life Objective: To determine the effects of therapeutic listening programme versus traditional music therapy on Depression and Quality of Life in Institutionalized Adolescents. Method: A single-center, single blinded, two group pretest-posttest randomized controlled trial of 36 institutionalized adolescents with depression will be recruited through the simple random sampling. Recruited institutionalized adolescents will be randomized into one of the two groups namely, therapeutic listening programme group and traditional music therapy group through block randomization. Both the groups will receive their respective interventions for 30 minutes a day, 2 days a week for 8 weeks. Participants in dance group performed, 30 minutes of dance for 3 days/week for 6 weeks. The primary outcome measures will be Children’s Depression Inventory (CDI) and Youth Quality of Life Instrument – Short Form (YQOL-SF). Urine test and electroencephalogram (EEG) will be recorded in addition to CDI and YQOL-SF. All the outcome measures will be measured at baseline and 8 weeks post intervention. Results: Normality of the collected data will be analyzed using Shapiro-Wilk test of normality. Descriptive statistics will be expressed in mean±Standard deviation/mean (95% confidence interval) with range and parametric tests/non-parametric tests, paired t-test/Wilcoxon signed rank test and independent t-test/MannWhitney U-test will be used for within and between group comparisons based on normality. Conclusion: The study outlines the importance of therapeutic listening programme on institutionalized adolescents with depression. Successful completion of this RCT will create evidence on the best treatment options for institutionalized adolescents with depression